Pengaruh Model Pembelajaran Creative Problem Solving dengan Pendekatan STEM Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika - Inayatul Maula, Siti; Baalwi, Muhammad Assegaf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is one of the essential subjects that plays a vital role in developing students’ logical, analytical, and systematic thinking skills. One of the main goals of mathematics education is to enhance students’ problem-solving abilities. This study aims to determine the effect of the STEM (Science, Technology, Engineering, and Mathematics) approach with the Creative Problem Solving (CPS) learning model on mathematical problem-solving abilities in division material. The subjects of the study were grade III students of SDN Gelang 1 Tulangan, Sidoarjo in the 2024-2025 academic year with a sample size of 15 students. The study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research instrument was a mathematical problem-solving ability test that had been validated with a Cronbach alpha value of 0.874. The results showed that there was a significant effect of the STEM approach with the Creative Problem Solving learning model on mathematical problem-solving abilities, indicated by the significance value of the paired sample t-test of 0.000 (p <0.05). The increase in students' mathematical problem-solving abilities was evidenced by an increase in the average score from 42 in the pretest to 80 in the posttest, with an increase of 38 points (90.5%). These results are in line with previous studies that also showed the effectiveness of similar approaches in improving mathematical problem-solving abilities at various levels of education. This study contributes to the development of innovative mathematical learning models for elementary school students.